Novel Method for Real Time Co‐Registration of IVUS and Coronary Angiography. (29th January 2016) - Frimerman, Aharon; Abergel, Eitan; Blondheim, David S.; Shotan, Avraham; Meisel, Simcha; Shochat, Michael; Punjabi, Pritesh; Roguin, Ariel
Abstract : Objectives: We present our experience with a novel method for real time co‐registration of intravascular ultrasound (IVUS) and coronary angiography. Background: A major limitation of the current practice of concomitant use of coronary angiography and IVUS is that the locations of the acquired IVUS images are not correlated with their exact locations on the vessel roadmap obtained by coronary angiography. Methods: Phantoms simulating the coronary tree were used to test the accuracy and potential of co‐registration. Subsequently we examined patients who underwent IVUS during cardiac catheterization. Analysis and feasibility were performed in 42 arteries of 36 patients. Results: The statistical validation in phantoms resulted in a co‐registration accuracy of 1.12 mm. The length measurement on an angiogram resulted in an accuracy of 0.38 mm. Co‐registration in patients was successful in all cases and four categories were assisted by 1(bad) to 5 (good) grading. Accuracy (the co‐registration precision in pointing at the exact corresponding location): 4.8±0.41; Ease of use and workflow: 4.74±0.44; Stent landing zone detection and evaluation: 4.58±0.5; Stent landing zone length and diameter measurement: 4.94±0.23. The co‐registration error was estimated as no more than 1 mm. Conclusion: In this pilot study, we found that the novel IVUS and coronary angiography co‐registration method is accurate, easy to use, fast and user‐friendly. This method precludes the need to use motorized automated pull back device. (J Interven Cardiol 2016;29:225–231)